Herramienta de Simulación Financiera para la toma de Decisiones en las Sociedades de Acciones Simplificadas S.A.S del Cantón Latacunga, Provincia de Cotopaxi. - Chango Pilaluisa, Irma Elizabeth (2023)
The present research work presents a quantitative approach, with a documentary bibliographic modality, presenting an exploratory, descriptive and correlational methodological level in relation to the financial management of 60 Sociedades de Acciones Simplificadas S.A.S of the Latacunga canton, this is how its problems are described. where the growth in its activities was observed but due to the poor interpretation of the financial statements it is directly related to the lack of practical tools to understand the current situation of your organization to make adequate decisions, in this way the investigation was based on proposing the strengthening decision-making in the financial area through a financial simulation tool. It was possible to build an epistemological and conceptual theoretical support applied to the variables of decision making and financial management where the inductive method prevailed, since particular premises were used, that is, the application of each financial indicator, to reach a general conclusion, which is the global diagnosis of each Simplified Share Company. A modeling of each financial indication was presented based on the utility curves methodology.